A review on integration of lightweight gradient lattice structures in additive manufacturing parts. (June 2020) - Seharing, Asliah; Azman, Abdul Hadi; Abdullah, Shahrum
This review analyses the design, mechanical behaviors, manufacturability, and application of gradient lattice structures manufactured via metallic additive manufacturing technology. By varying the design parameters such as cell size, strut length, and strut diameter of the unit cells in lattice structures, a gradient property is obtained to achieve different levels of functionalities and optimize strength-to-weight ratio characteristics. Gradient lattice structures offer variable densification and porosities; and can combine more than one type of unit cells with different topologies which results in different performances in mechanical behavior layer-by-layer compared to non-gradient lattice structures. Additive manufacturing techniques are capable of manufacturing complex lightweight parts such as uniform and gradient lattice structures and hence offer design freedom for engineers. Despite these advantages, additive manufacturing has its own unique drawbacks in manufacturing lattice structures. The rules and strategies in overcoming the constraints are discussed and recommendations for future work were proposed.